An Arctic Paradox: Response of Fluvial Hg Inputs and Bioavailability to Global Climate Change in an Extreme Coastal Environment - Lacerda, Luiz Drude de; Marins, Rozane Valente; Dias, Francisco José da Silva (Frontiers in Earth Science, 2020)
Global climate change interacts with regional alterations of land use in coastal basins and promotes rapid changes in the biogeochemistry of the coastal zone. These changes are generally stronger in extreme environments such as polar and semiarid regions. In these environments, biogeochemical changes result in a greater transfer of pollutants from the continent to the sea with resultant contamination of marine biota. In semiarid regions, there is a reduction in continental runoff and bulk pollutant transport, but paradoxically, there is an increase in the export of more bioavailable pollutants, resulting in higher contamination of the marine biota. In tropical latitudes, mangroves dominate coastal and estuarine environments and respond rapidly to environmental changes. The semiarid coast of Brazil is strongly affected by climate change. A major environmental response is altered hydrodynamics, generally involving decreasing continental runoff to the ocean, caused by reducing annual rainfall and damming of rivers. Also, strengthening of marine forcing due to heat accumulation in the South Atlantic Ocean and rising sea level pushes shelf and coastal waters into estuaries. Basin and oceanic processes undergo positive feedback, which causes an increase in the water residence time in estuaries, an extension of saline intrusion landward, accumulation of sediments in the inner reaches of estuaries, and the expansion of mangrove areas, particularly over the past 50 years. Expansion of mangroves means an expansion of sulfate reduction metabolism, which produces large amounts of dissolved organic carbon, characterized by a high capacity for forming organo-metallic complexes of high environmental significance. Dissolved and particulate Hg concentrations and fluxes are greater from the river to the estuary than from the estuary to the sea, producing an accumulation of particulate Hg in the estuary. Particulate Hg export may occur only during extremely rainy periods, and Hg is eventually deposited is shelf sediments, displaying low bioavailability. Export of dissolved, reactive, and DOC-bound Hg is practically nonexistent during rainy periods but increases by two orders of magnitude during the progressively longer dry periods. These highly bioavailable forms of Hg will enter food webs in the lower estuary and coastal areas, increasing contamination of the biota and human exposure to Hg.